Tomboys and lesbians the Filipino female homosexual and her identity development process. [article]. - Ofreneo, Mira Alexis P. .
This research explores how the female homosexual in Philippine culture experiences and cognizes her sexuality and how she assumes and accepts a homosexual identity. Using the case study method, 12 self-identified female homosexual (6 late adolescents and six young adults) were interviewed. Results reveal in an ideal three-stages model of a Filipino female homosexual identity development: (a)awareness of homosexual orientation through gender nonconformity and initial homosexual feelings; (b)trying out a homosexual orientation as reflected in homosexual peer groups, romantic relationships, and sex; (c)choosing a homosexual identity. A salient finding is how tomboy, the cultural label for a stereotypically masculine female homosexual, shapes early identification and later development creating two distinct groups-the tomboys and the lesbians.